UJI KARAKTERISTIK FISIK DAN HEDONIK DARI ANTIAGING SLEEPING MASK DENGAN EKSTRAK KULIT BUAH DELIMA MERAH - Djati Wulan Kusumo; Zurotul Muarifah; Fransisca Dita Mayangsari (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
ABSTRACT Red pomegranate peel extract (RPPE) contains ellagitannin. This compound has an antioxidant effect. Therefore,this extract has good potential as an active ingredient in anti-aging cosmetics. However, applying the extract directly to the skin is inconvenient. So in this study RPPE was formulated into a sleeping mask. This study aims to analyze the effect of variations in the concentration of RPPE in sleeping masks on physical characteristics and the level of preference/hedonic. RPPE concentration observed was 2.5% (F1) ; 5% (F2) ; 7.5% (F3). Characteristic tests include organoleptic, pH value, visual homogeneity, consistency and viscosity. Parameters analyzed in the hedonic test include texture, color, and aroma. The organoleptic and homogeneity were analyzed descriptively. The test data for pH and viscosity were analyzed statistically using the One Way ANOVA method. The results of the hedonic test were analyzed statistically using the univariate method. Based on the results of the organoleptic test, it is known that F1 have a light brown color, F2 is brown, and F3 is dark brown. The third formula is visually homogeneous. The higher the concentration of RPPE, the lower the pH value and viscosity of the preparation. Increasing the concentration of RPPE reduce consistency. This study concluded that the concentration of RPPE affects the physical properties of the aspects of color, consistency, pH, and viscosity. The concentration of RPPE also affects the level of preference of the panelists. Most of the panelists prefer the color and texture of the sleeping mask that contains low concentration of RPPE (2.5%). Keywords : Physical Characteristics ; Hedonic; Sleeping Mask ; Red Pomegranate Peel Extract